Parental Empowerment in a Primitive Reflex Integration Program Targeting the Gross Motor Skills of Children with Physical Disabilities at the Jambi City Special School (SLB) - Wanti Hasmar; Faridah Faridah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Primitive reflexes are automatic, stereotyped movements controlled by the brainstem that do not require cortical (conscious) involvement. These reflexes are movement patterns that occur spontaneously in newborns and must be integrated as motor development matures. Normally, these reflexes disappear as the child ages and acquires new abilities. Failure to exhibit age-appropriate reflex patterns raises suspicion of developmental disorders resulting from brain injury. This community service initiative aimed to educate teachers at the Jambi City Special School (SLB) regarding primitive reflex integration and its role in child development. The program employed lectures, discussions (Q&A sessions), and demonstrations of primitive reflex integration techniques, conducted between March and September 2024. The target audience consisted of teachers at SLB Negeri Sri Soedewi, with the goal of ensuring they understood the concepts of primitive reflex integration in child development. The initiative sought to inform teachers at SLB Negeri Sri Soedewi about using game-based primitive reflex integration activities to enhance the development of female elementary students with physical disabilities; the sessions lasted 45–60 minutes and involved 10 participating teachers. The outcome was an increase in the teachers' knowledge regarding primitive reflex integration in child development, as well as their ability to successfully re-demonstrate the integration techniques